Literature Review of the Relationship between Positive Law Implementation and Social Inequality in Indonesia: A Case Study on National Land Policy - Safnul, Dody; Wahyu, Ahmad Braja; Cahyandi, Cahyandi; Hasibuan, Rabiah Adawiyah; Akbar, Maqbul; Maulana, Rico; Kurniawan, Wahyudi; Bakti, Ali; Nainggolan, Riswaldi; Rahmat, Tomy Aldista (PT FORMOSA CENDEKIA GLOBAL, 2025)
Positive law in Indonesia is often considered a neutral and objective system. However, in its implementation, this law sometimes creates social inequality, especially in national land policy. This study aims to analyze the relationship between positive law implementation and social inequality using a case study approach on agrarian reform policies and forced evictions in urban areas. This study uses a qualitative method with data collection techniques in the form of in-depth interviews, document studies, and thematic analysis. The results of the study show that the implementation of positive laws often does not pay attention to social realities, thus creating injustice for marginalized communities. This research provides recommendations for more inclusive legal policy reforms, in order to create more equitable social justice.